The Impact of Mobile Technology on Managerial Communication and Decision-Making: Enhancing Efficiency and Strategic Agility - Fatema Said Al-Burtamanai, Sallam O. F. Khairy (Journal of Computational Analysis and Applications (JoCAAA), 2025)
The power of mobile technology in the realm of managerial communication and making decisions has ushered in a new era of efficiency, collaboration, and strategic agility. This paper focuses on the implications of mobile tools like smartphones, instant messaging, and cloud-based applications on managerial practice. Mobile technology facilitates real-time communication and access to data, leading to increased decision-making speed and responsiveness. However, challenges such as information overload, cybersecurity risks, and work-life imbalance pose significant concerns. This research analyses how mobile information technology adoption affects managerial effectiveness using the Media Richness Theory and the Technology Acceptance Model. Using quantitative and qualitative analyses of secondary data (reports and empirical studies), trends and best practices on a given topic are reviewed. It is found that mobile technology increases managerial efficiency; however, strategies need to be put in place to limit the risk. It contributes to understanding the future of management using mobile technology by providing recommendations on how to make use of it in a corporative file.